1987
DOI: 10.1177/07399863870092005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Short Acculturation Scale for Hispanics

Abstract: This article reports the development of a short (12-item) acculturation scale for Hispanics. Separate factor analyses of the responses of 363 Hispanics and 228 non-Hispanic whites produced three factors: "Language Use," "Media," and "Ethnic Social Relations." The 12-item scale (explaining 67.6% of the variance for Hispanics) correlated highly with the following validation criteria: respondents' generation, length of residence in the U.S., age at arrival, ethnic self-identification, and with an acculturation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
1,492
4
9

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,911 publications
(1,532 citation statements)
references
References 19 publications
27
1,492
4
9
Order By: Relevance
“…Despite controversies regarding the measurement of acculturation, the results from the current study suggest the benefits of this four-item scale as a brief measure of acculturation, particularly when this measure is combined with data regarding length of stay in the United States, country of birth, and language use during face-to-face interviews. These results further support Marin et al 's original assertion that language alone can be used as a measure of acculturation, especially when measuring all the dimensions of acculturation is impractical and may prevent other researchers from measuring acculturation at all (4,20,29). Future research should include a larger and more evenly distributed sample where multivariate methods such as regression analyses could be used to examine potential predictors of acculturation including age, parity, social support, country of origin, and length of time in the United States.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Despite controversies regarding the measurement of acculturation, the results from the current study suggest the benefits of this four-item scale as a brief measure of acculturation, particularly when this measure is combined with data regarding length of stay in the United States, country of birth, and language use during face-to-face interviews. These results further support Marin et al 's original assertion that language alone can be used as a measure of acculturation, especially when measuring all the dimensions of acculturation is impractical and may prevent other researchers from measuring acculturation at all (4,20,29). Future research should include a larger and more evenly distributed sample where multivariate methods such as regression analyses could be used to examine potential predictors of acculturation including age, parity, social support, country of origin, and length of time in the United States.…”
Section: Discussionsupporting
confidence: 83%
“…Cobas and his colleagues found that when they used the Cuellar (19) acculturation scale to reanalyze 1989 Scribner and Dwyer Hispanic negative birth outcome data, the four language items on the scale loaded higher than ethnic identification for both prediction of smoking and lowbirthweight status (20,23,24). This analysis further reinforces the premise that language usage is a dominant factor in measuring levels of Hispanic acculturation.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The Short Acculturation Scale for Hispanics, adapted to include 5 of the 12 items focused on language, was used to measure acculturation [64]. Data suggest that this language-based version can be used independently as a measure of acculturation (Cronbach's alpha for the 5-item scale 5 0.90) [64].…”
Section: Acculturationmentioning
confidence: 99%